Pengaruh Beban Terhadap Putaran Turbin Helikal Untuk Pembangkit Tenaga Listrik - Antonius FA Silaen (MAJALAH TEKNIK SIMES, 2015)
Water turbine is a tool to convert kinetic energy into mechanical energy. This mechanical energy is converted into electrical energy by a generator. In a power generation system, water turbine is one of the main equipment in addition to the generator. This turbine is suitable for use on the free flow of kinetic energy to extract stream flow and irrigation. Testing water turbines that turn helical load-change, testing is performed at the irrigation flow Kemumu Village North Bengkulu. The results on the influence of the load on the turbine wheel helical water, the results are the combined data graph style Î”F against helical turbine rotation Figure 4.8 chart graph style combined the data processing, graph 4.8 shows the experimental research for smaller burden lies on the table load 4.3, a turbine wheel is smaller than 4.4 research while at the load force (Î”F) below the turbine rotation looks bigger than research 4.4 greater than studies 4.3